Building Cultural Capital in First‐Year Students at Residential Colleges and Universities. Issue 1 (April 2016) - Sinclair, Matthew S.; Erb, Natalee M.; Braxton, John M.
Abstract : College student persistence continues to be a vexing problem for colleges and universities. In Rethinking College Student Persistence (2014), Braxton, Doyle, Hartley, Hirshy, Jones, and McLendon explored the indirect role between cultural capital and first‐year student persistence. The significance of this role becomes more important when one considers the impact first‐year persistence has on the likelihood of graduation. The current article begins with an exploration of the indirect role of cultural capital in the persistence of first‐year persistence, then shifts focus to examining currently‐implemented practices and procedures at colleges and universities that are explicitly or implicitly designed to facilitate the development of cultural capital. These practices are recommended for institutions seeking to increase first‐year persistence, especially primarily residential institutions.